Animal Bones and Bone Artefacts from the Viking Age Site of Tornimäe in Saaremaa - Luik, Heidi; Maldre, Liina (Archaeologia Lituana, 2020)
Archaeological investigations in Tornimäe in the eastern part of the island Saaremaa took place in 1963, 1968 and 2004. Artefacts found during the excavations are mainly dated to the Viking Age. Most of the finds are pottery shards, some metal artefacts were found, and also animal bones. The majority of mammal bones are bones of domestic animals. Nearly half of these are caprine bones, bones of cattle, pig and horse are less numerous. Wild game bones are few, only seals were hunted more often. Bird and fish bones are also represented. Only a few bone artefacts were among the finds, more fragments of bone items were found among the animal bones during the identification of osteological material. The bone artefacts found in Tornimäe are rather simple items which do not require special skills from the bone worker and could have been made by the users of these artefacts. The uses of bone artefacts are well suited with the location of the site at the seashore.